Utilization of Ayurveda in Health Care: An Approach for Prevention, Health Promotion, and Treatment of Disease. Part 2-Ayurveda in Primary Health Care - HARI SHARMA, CHANDOLA, GURDIP SINGH, and GOPAL BASISHT (THE JOURNAL OF ALTERNATIVE AND COMPLEMENTARY MEDICINE Volume 13, Number 10, 2007, pp. 1135-1150, 2007)
Ayurveda is a comprehensive natural health care system that originated in India more than 5000 years ago. It is still widely used in India as a system of primary health care, and interest in it is growing worldwide as well. Ayurveda has unique concepts and methodologies to address health care throughout the course of life, from pregnancy and infant care to geriatric disorders. Common spices are utilized, as well as herbs, herbal mixtures, and special preparations known as Rasayanas. Purification procedures known as Panchakarma remove toxins from the physiology. Research has been conducted worldwide on Ayurveda. There are encouraging results for its effectiveness in treating various ailments, including chronic disorders associated with the aging process. Pilot studies presented in this paper were conducted on depression, anxiety, sleep disorders, hypertension, diabetes mellitus, Parkinson's disease, and Alzheimer's disease. These preliminary studies yielded positive results and provide a basis for conducting larger, more rigorous clinical trials. Conducting research that compares Ayurveda's comprehensive treatment approach, Western allopathic treatment, and an integrated approach combining the Ayurvedic and allopathic treatments would shed light on which treatment approach is the most effective for the benefit of the patient.